Determination of Individual Differences in Mental Imagery Tasks: An Approach to Visual Thinkers and Verbal Thinkers - Nishimura, Kazuo; Aoki, Takaaki; Inagawa, Michiyo; Tobinaga, Yoshikazu; Iwaki , Sunao (Recent Developments in Medicine and Medical Research Vol. 15, 2021)
The purpose of this study is to measure and analyze whether or not there is a significant difference in brain activity between individuals in imagery associated with spontaneous thinking using MEG. Specifically, we will compare visual thinking and verbal thinking in human spontaneous thinking, and discuss their relationship to brain activity. In a recent study, we divided subjects into visual and non-visual thinking types by questionnaire, gave them a verbal task and a visual task, and measured them by MEG. The results showed that there were significant differences in brain activation near the primary visual area and near the frontal language area [1]. This suggests that our natural thinking characteristics may be divided into two types: visual and verbal. Thus, by analyzing the diversity of thinking characteristics of individuals, it would be possible to apply the research results to education, career choice and other fields [2].